Digital Authoritarianism and the Erosion of Civil Liberties: A Comparative Legal Study of Surveillance Laws in China, India, and the United States - Joshua Lee; Zhang Mei; Kunal Mehta (Artes Libres Institutum, 2025)
As governments increasingly adopt digital surveillance technologies, concerns are mounting over the erosion of civil liberties and democratic accountability. This paper conducts a comparative legal analysis of surveillance frameworks in China, India, and the United States—three major powers with distinct legal systems but converging practices in state surveillance. It explores how legal justifications of national security, public order, and counterterrorism are used to expand state control over digital spaces, often at the cost of privacy, freedom of expression, and minority rights. The novelty of this research lies in its juxtaposition of authoritarian and democratic regimes to reveal a troubling global convergence toward digital authoritarianism. Rather than focusing solely on authoritarian states, this paper interrogates how even liberal democracies are adopting surveillance measures that bypass judicial oversight and erode constitutional protections. This paper contributes to global debates on technology, law, and governance by framing digital surveillance as a trans-systemic legal issue rather than a regime-specific anomaly. It critiques the inadequacy of current international human rights frameworks in regulating surveillance technologies and proposes a set of normative and legal principles to safeguard digital civil liberties. By offering a cross-jurisdictional analysis grounded in constitutional law, human rights theory, and digital ethics, this study calls for an urgent international legal response to surveillance overreach. It concludes with policy recommendations for building a rights-based global regulatory framework, including stronger transparency obligations, oversight mechanisms, and digital rights treaties.